C332C Genotype of Glyoxalase 1 and its Association with Late Diabetic Complications - Groener, J. B.; Reismann, P.; Fleming, T.; Kalscheuer, H.; Lehnhoff, D.; Hamann, A.; Roser, P.; Bierhaus, A.; Nawroth, P. P.; Rudofsky, G. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Glyoxalase 1 catalyses the detoxification of methylglyoxal, a major precursor of advanced glycation end products associated with aging, neurodegenerative diseases, and microvascular complications of diabetes. Here, we examine a possible association of a single nucleotide polymorphism of glyoxalase 1 gene (Glo1 A332C, rs4746 or rs2736654) with the prevalence of microvascular diabetic complications in patients with type 1 and type 2 diabetes.Genotyping was performed in 209 patients with type 1 and 524 patients with type 2 diabetes using polymerase chain reaction and subsequent cleavage by restriction endonuclease Bsa I.Frequencies of the glyoxalase 1 genotypes were different with respect to diabetes type with a significantly higher prevalence of A332A-genotype in type 1 diabetes (35.9% vs. 27.3%; p=0.03). In type 1 diabetes, there was no correlation of any genotype with diabetic retinopathy, nephropathy or neuropathy. In contrast, type 2 diabetic patients homozygous for the C332C allele showed a significantly increased prevalence of diabetic neuropathy (p=0.03; OR=1.49 [95%-CI: 1.04; 2.11]), while no association with diabetic nephropathy or retinopathy was found. However, the significance of this association was lost after correction for multiple testing.Our data suggest a possible association of C332C-genotype of the glyoxalase 1 gene with diabetic neuropathy in type 2 diabetes, supporting the hypothesis that methylglyoxal might be an important mediator of diabetic neuropathy in type 2 diabetes.
Keywords: diabetic neuropathy; detoxification; methylglyoxal; diabetes; Glo1 A332C; rs4746